2014
DOI: 10.1002/ejsp.2063
|View full text |Cite
|
Sign up to set email alerts
|

A step too far? Leader racism inhibits transgression credit

Abstract: Prior research established that when in-group leaders commit serious transgressions, such as breaking enforceable rules or engaging in bribery, people treat them leniently compared with similarly transgressive regular group members or out-group leaders ('transgression credit'). The present studies test a boundary condition of this phenomenon, specifically the hypothesis that transgression credit will be lost if a leader's action implies racist motivation. In study 1, in a corporate scenario, a transgressive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…We also established various boundary conditions for this “ transgression credit ,” namely that the leader must be seen to want to serve the group's interests (cf. Packer, Miners, & Ungson, ), not to cross significant moral boundaries, such as expressing racist sentiment (Abrams, Travaglino, Randsley de Moura, & May, ; cf. Brescoll, Okimoto, & Vial, ), and to be part of a relatively small group (Travaglino, Abrams, Randsley de Moura, & Yetkili, ; cf.…”
Section: Subjective Group Dynamics Theory and Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…We also established various boundary conditions for this “ transgression credit ,” namely that the leader must be seen to want to serve the group's interests (cf. Packer, Miners, & Ungson, ), not to cross significant moral boundaries, such as expressing racist sentiment (Abrams, Travaglino, Randsley de Moura, & May, ; cf. Brescoll, Okimoto, & Vial, ), and to be part of a relatively small group (Travaglino, Abrams, Randsley de Moura, & Yetkili, ; cf.…”
Section: Subjective Group Dynamics Theory and Leadershipmentioning
confidence: 99%
“…To date, the roles of accrual and conferral processes in transgression credit have not been demonstrated empirically. In this article, we present data that were collected as part of our studies on transgression credit (Abrams et al., , ) but were not published earlier due to journal editorial preferences and space limitations. Because the original studies were reported in detail, the present article provides only a summary of their methodology and findings, focusing instead on new analyses examining mediational processes.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, due to the perception of ingroup homogeneity and thereby stronger self‐stereotyping, members of smaller groups endorse ingroup attributes more strongly than members of larger groups (Simon & Hamilton, ). As ingroup leaders are perceived as embodying those attributes more than other members (Hogg, ), members of smaller groups may be more sensitive to how leaders’ actions reflect on them (Abrams et al ., ). This line of reasoning is also consistent with the idea that members of smaller groups are more prone to embarrassment (Buss, ), due to the fact that they are more self‐attentive, and more likely to attract attention from other (larger) groups (Mullen, ).…”
Section: Introductionmentioning
confidence: 97%
“…In this sense, it might also be interesting to compare the effects of different levels of disrespect on trust in the political system. In their studies, Abrams and colleagues (Abrams, Travaglino, Randsley de Moura, & May, ) found, for instance, that study participants did not accept racism, neither from in‐group nor from out‐group leaders. With Trump as a president, who himself does not hesitate to attack Hispanics or Muslims in very disrespectful ways, there will be many interesting research occasions in the future to replicate this finding in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%